Modified ZSM-5 molecular sieve as well as preparation method and application thereof
By calcining and modifying the waste liquid containing titanium tetrachloride with ZSM-5 molecular sieve and phosphorus source, the problem of waste liquid treatment during the catalyst preparation process and the problem of insufficient thermal stability of ZSM-5 molecular sieve is solved, and waste liquid recovery and molecular sieve performance are achieved.
Patent Information
- Application Number
- CN202311423665.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The problem of treating waste liquids containing titanium tetrachloride generated during the preparation of polypropylene catalysts and the insufficient thermal stability of ZSM-5 molecular sieve affects its application in cracking catalysts.
By calcining and modifying the waste liquid containing titanium tetrachloride produced during the preparation of the titanium-based polypropylene catalyst as raw materials, it is calcined and modified with the ZSM-5 molecular sieve and the phosphorus source to form a modified ZSM-5 molecular sieve. This method not only solves the problem of waste liquid treatment, but also improves the hydrothermal stability and catalytic selectivity of molecular sieves.
It realizes effective recycling and treatment of waste liquid, improves the hydrothermal stability and catalytic performance of modified ZSM-5 molecular sieve, and reduces environmental pollution and resource waste.
Smart Images

Figure BDA0004522167610000111 
Figure BDA0004522167610000121 
Figure BDA0004522167610000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst materials, and in particular to a modified ZSM-5 molecular sieve and a preparation method and application thereof. Background Art
[0002] In the process of industrial production of polyolefins, the widely used catalyst is mainly Ziegler-Natta catalyst, which is a titanium catalyst. Regarding the preparation of titanium polyolefin catalysts, for example, CN 102336851 A discloses a propylene polymerization catalyst, including magnesium, titanium, halogen and internal electron donor compounds diisobutyl phthalate, diethyl phthalate or di-n-butyl phthalate and a mixture of succinate; CN 107434832A discloses a propylene polymerization catalyst, mainly composed of an alcohol magnesium compound, a titanium compound and a phosphate electron donor compound. The common method for preparing titanium catalysts at present is: first, the preparation of magnesium halide alcoholate is carried out, for example, after the magnesium halide and alcohol are heated and dissolved, high pressure ejection or high-speed stirring is used, and the method of solidifying into microsphere particles in a cooling medium is obtained, and the specific steps are referred to the relevant description in CN1110281A; then the magnesium halide alcoholate particles are reacted with a halogen-containing compound such as titanium tetrachloride to prepare a magnesium-supported catalyst, during which various promoters can be added for modification. In the above-mentioned catalyst preparation process, a large amount of titanium tetrachloride needs to be used, and the excess ratio is very large. At the same time, the obtained solid catalyst component needs to be washed with a hydrocarbon solvent (such as hexane) to remove the unloaded titanium tetrachloride therein. Therefore, in the polyolefin catalyst production process, after the catalyst solid is separated and precipitated, a large amount of catalyst mother liquid containing titanium tetrachloride, unreacted hydrocarbons, unreacted halogenated alkoxy titanium, alkoxy magnesium, unreacted esters, etc. is generated. A large amount of waste liquid containing titanium tetrachloride is generated in the titanium-based polypropylene catalyst preparation process, wherein the titanium tetrachloride content is about 80%-95% (by weight), the alkoxy titanium complex is about 2%-5%, and the remainder is hydrocarbons containing n-hexane and esters, wherein n-hexane accounts for the majority of hydrocarbons. If the above-mentioned waste liquid containing titanium tetrachloride is discharged into the environment, it will inevitably cause environmental pollution and waste of resources. At present, there is a lack of simple and effective methods for recycling and treating waste liquid containing titanium tetrachloride and reducing environmental pollution.
[0003] The existing ZSM-5 molecular sieve has low thermal stability. Even after being modified by known methods, the thermal stability of the ZSM-5 molecular sieve is still not ideal, which is not conducive to the use of the molecular sieve, especially the use of the molecular sieve as a cracking catalyst. It is necessary to provide a method for improving the thermal stability of the modified ZSM-5 molecular sieve.
[0004] In the prior art, CN102114429A discloses a method for increasing the B acid amount of ZSM-5 molecular sieve and achieving increased production of light olefins, which is by modifying the ZSM-5 molecular sieve with iron and titanium at the same time, and the mass ratio of iron to titanium in the modified molecular sieve is 0.3-3:1, so that the catalytic reactivity of the molecular sieve is improved, and the conversion of long-chain alkanes and aromatic hydrocarbons with long-chain alkyl side chains such as isopropylbenzene is promoted, and the yield of light olefins is increased. US5171921 discloses a method for modifying ZSM-5 molecular sieves, which includes exchanging the synthesized ZSM-5 molecular sieve for sodium reduction, drying, and roasting, and then modifying, drying, and roasting with phosphoric acid to obtain a phosphorus-containing ZSM-5 molecular sieve.
[0005] The prior art does not involve the treatment of waste liquid containing titanium tetrachloride generated during the preparation of titanium-based polypropylene catalysts. Furthermore, the modified ZSM-5 molecular sieve does not involve improving the stability of the molecular sieve or the stability of the molecular sieve is not ideal.
[0006] Therefore, in order to solve the problem of treating a large amount of waste liquid containing titanium tetrachloride generated during the preparation of polypropylene catalysts and to solve the unfavorable factor of poor hydrothermal stability during the use of molecular sieves, a new molecular sieve preparation technology with simple and feasible preparation process and excellent performance is needed. Summary of the invention
[0007] In order to solve the above problems, the purpose of the present invention is to provide a modified ZSM-5 molecular sieve and its preparation method and application. The modified ZSM-5 molecular sieve provided by the present invention has a high specific surface area retention rate after aging, and has high hydrothermal stability and catalytic selectivity.
[0008] In order to achieve the above object, the present invention provides a method for preparing a modified ZSM-5 molecular sieve, the preparation method comprising: mixing a titanium source and a raw material ZSM-5 molecular sieve to form a mixed solution, and performing a first roasting; or, fully impregnating the raw material ZSM-5 molecular sieve with an impregnation solution containing a titanium source, drying, and performing a first roasting;
[0009] The product of the first calcination is mixed with a phosphorus source and subjected to a second calcination to obtain the modified ZSM-5 molecular sieve.
[0010] In the above preparation method, the titanium source and the phosphorus source can jointly modify the ZSM-5 molecular sieve, synergistically improving the acid distribution and hydrothermal stability in the molecular sieve, thereby promoting the heavy oil conversion in the catalytic process involving the modified ZSM-5 molecular sieve and reducing the amount of coke.
[0011] In the above preparation method, the titanium source refers to a substance containing titanium element, and specifically may include titanium tetrachloride. Further, the titanium source may include a combination of titanium tetrachloride and hexane. In some specific embodiments, the weight ratio of titanium tetrachloride to hexane may be (4-34):1, for example, 4:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 34:1 and other specific values, and a range with any two of the above specific values as endpoints.
[0012] According to a specific embodiment of the present invention, the titanium source may specifically include waste liquid containing titanium tetrachloride. The waste liquid containing titanium tetrachloride contains titanium tetrachloride and may further contain hydrocarbons such as hexane.
[0013] According to a specific embodiment of the present invention, the titanium tetrachloride-containing waste liquid can be a titanium tetrachloride-containing waste liquid obtained in the production process of titanium-based polyolefin (such as polypropylene) catalyst; the titanium tetrachloride-containing waste liquid produced by titanium-based polyolefin catalyst is obtained in the process of preparing polyolefin catalyst, and based on the weight of the titanium tetrachloride-containing waste liquid as 100%, the titanium tetrachloride-containing waste liquid contains 80%-95% titanium tetrachloride, 2%-5% alkoxy titanium complex, and the remainder is hydrocarbon; wherein the hydrocarbon is liquid at room temperature, and the hydrocarbon includes hexane and esters, most of which are hexane.
[0014] In the above waste liquid containing titanium tetrachloride, titanium tetrachloride can be used to modify ZSM-5 molecular sieves; hexane can promote the uniform distribution of titanium in ZSM-5 molecular sieves, increase the pore volume of modified ZSM-5 molecular sieves, and thus improve the diffusion effect of molecules in modified ZSM-5 molecular sieves and improve the catalytic reaction selectivity of modified ZSM-5 molecular sieves. In addition, hydrocarbons such as hexane present in the titanium tetrachloride solution can form micropores, mesopores, etc. after calcination, which is beneficial to improve the pore structure of the catalyst and improve the catalytic reaction selectivity.
[0015] The preparation method uses a large amount of waste liquid containing titanium tetrachloride generated in the preparation process of the titanium-based polypropylene catalyst as a raw material, thereby solving the problem of waste liquid treatment, saving treatment costs and avoiding environmental pollution.
[0016] In the above preparation method, the phosphorus source may include one or a combination of two or more of phosphoric acid, phosphate, phosphorous acid, phosphite, pyrophosphoric acid, pyrophosphate, polyphosphoric acid, polyphosphate, metaphosphoric acid, and metaphosphate. Further, the phosphorus source may include one or a combination of two or more of phosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen phosphate, magnesium phosphate, aluminum phosphate, phosphorous acid, ammonium phosphite, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.
[0017] In the above preparation method, based on the weight of the modified ZSM-5 molecular sieve being 100%, the modified ZSM-5 molecular sieve may include 0.2%-25% titanium and 0.2%-6% phosphorus; wherein the weight of the titanium and phosphorus are calculated as oxides (titanium dioxide, phosphorus pentoxide).
[0018] In the above preparation method, the modified ZSM-5 molecular sieve may also include a modified metal element, and accordingly, the raw material of the modified ZSM-5 molecular sieve may also include a modified metal source, and the modified metal source is used to provide the modified metal element. The modified metal element can modify the ZSM-5 molecular sieve to improve the hydrothermal stability, acidity and catalytic reaction performance of the ZSM-5 molecular sieve. In some specific embodiments, the modified metal element includes one or more combinations of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium. In some specific embodiments, the modified metal element may specifically include zirconium and / or iron, etc.
[0019] According to a specific embodiment of the present invention, the weight content of the modified metal element in the modified ZSM-5 molecular sieve may be 0-5%, for example, greater than 0% and less than or equal to 5%, calculated as oxide of the modified metal element.
[0020] According to a specific embodiment of the present invention, based on the weight of the modified ZSM-5 molecular sieve being 100%, the modified ZSM-5 molecular sieve may include 0.2%-25% of titanium, 0.2%-6% of phosphorus and 0-5% of modified metal elements, wherein the weights of titanium, phosphorus and modified metal elements are respectively calculated as oxides.
[0021] In the above preparation method, the modified metal source can be added to the mixed solution and / or the impregnation solution. That is, the modified metal source can be mixed with the titanium source and the raw material ZSM-5 molecular sieve to form a mixed solution, or can be mixed with the titanium source to form an impregnation solution for impregnating the raw material ZSM-5 molecular sieve, and then mixed with the phosphorus source after the first roasting. By adopting the above reaction sequence, precipitation between the phosphorus source and the titanium source and the modified metal source can be avoided.
[0022] In the above preparation method, the modified metal source may specifically include metal oxides and / or metal salts. The metal salts include one or a combination of two or more of chlorides, nitrates, carbonates, sulfates, oxalates, and acetates.
[0023] In the above preparation method, the silicon-aluminum ratio (molar ratio of silicon dioxide and aluminum oxide) of the raw material ZSM-5 molecular sieve can be 15-450. In some specific embodiments, the silicon-aluminum ratio of the raw material ZSM-5 molecular sieve can be a ZSM-5 molecular sieve with a relatively high silicon-aluminum ratio, for example, the silicon-aluminum ratio of the raw material ZSM-5 molecular sieve can be 20-450, 30-450, etc.
[0024] In the above preparation method, the raw material ZSM-5 molecular sieve may include a micromesoporous ZSM-5 molecular sieve, that is, a molecular sieve containing both micropores and mesopores; in some specific embodiments, the mesopore volume of the micromesoporous ZSM-5 molecular sieve may be no less than 0.10 mL / g, for example, 0.10-0.70 mL / g, 0.10-0.30 mL / g, 0.30-0.70 mL / g, etc.
[0025] In some specific embodiments, the raw material ZSM-5 molecular sieve may be added in the form of a slurry, which may be formed by dispersing the raw material ZSM-5 molecular sieve in water.
[0026] In the above-mentioned method for preparing the ZSM-5 molecular sieve, the pH value of the mixed solution and / or the impregnating solution can be controlled to be 0.5-8, for example, 0.5-3. The present invention is beneficial to control the distribution of titanium in the ZSM-5 molecular sieve by controlling the pH value range. In some specific embodiments, the pH value of the mixed solution can be 0.5, 1, 1.5, 1.8, 2, 3, 4, 5, 6, 7, 8 and other specific values, as well as a range with any two of the above specific values as endpoints.
[0027] According to a specific embodiment of the present invention, the above-mentioned preparation method may also include adjusting the pH value of the titanium source to 0.5-8, and then mixing the titanium source with the ZSM-5 molecular sieve. When the raw material includes a modified metal source, the above-mentioned preparation method may also include adjusting the pH value of the modified metal source to 0.5-8, for example, 0.5-3, and then mixing the modified metal source with the ZSM-5 molecular sieve. By pre-adjusting the pH value of the titanium source and the modified metal source, it is possible to avoid the molecular sieve dealumination caused by the excessive acidity of the system when the titanium source, the modified metal source and the ZSM-5 molecular sieve are mixed. In addition, by controlling the pH value range, the distribution of modifying elements such as titanium in the ZSM-5 molecular sieve can be controlled.
[0028] In some specific embodiments, the pH value can be adjusted by a pH adjuster, and the pH adjuster includes an alkaline substance. The alkaline substance can include one or a combination of two or more of ammonia water, ammonium carbonate, ammonium bicarbonate, water glass, magnesium oxide, magnesium hydroxide, and magnesium carbonate.
[0029] According to a specific embodiment of the present invention, the preparation method may include: adjusting the pH value of the titanium source and the modified metal source to 0.5-8, filtering, and then mixing the filter cake obtained by filtration with the raw material ZSM-5 molecular sieve.
[0030] In the above preparation method, the mixed solution and / or the impregnation solution may further include a dispersant. The dispersant can promote the full dispersion of the modified metal element and the titanium element, which is beneficial to improving the hydrothermal stability of the modified ZSM-5 molecular sieve.
[0031] In some specific embodiments, the weight of the dispersant can be 0-20% of the weight of the raw material ZSM-5 molecular sieve, and can be further controlled to be 0.2%-20%, 0-10%, 0.3-6%. In some specific embodiments, the weight ratio of the dispersant to the raw material ZSM-5 molecular sieve can be 0.1%, 0.2%, 0.3%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20% and other specific values, and a range in which any two of the above specific values are endpoints.
[0032] In the above preparation method, the dispersant includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.
[0033] In the above preparation method, the dispersant can be added once or in several portions. Specifically, when the dispersant is added once, the dispersant can be added to the mixed solution and / or the impregnation solution, that is, the dispersant is added together with the titanium source and the modified metal source. This addition method helps to improve the dispersibility of the titanium element and the modified metal element; alternatively, the dispersant can also be added together with the phosphorus source. This addition method can improve the dispersibility of the phosphorus element. When the dispersant is added in several portions, part of the dispersant can be added to the mixed solution containing the titanium source, the modified metal source, and the raw material ZSM-5 molecular sieve or the impregnation solution containing the titanium source and the modified metal source, and the remaining dispersant can be added together with the phosphorus source to achieve the effect of improving the dispersibility of titanium, phosphorus, and the modified metal elements in the molecular sieve.
[0034] The preparation method of the modified ZSM-5 molecular sieve has no special restrictions on the mixing conditions of the titanium source and the raw material ZSM-5 molecular sieve, and the mixing conditions of the first calcined product and the phosphorus source, as long as the components are fully mixed. In some specific embodiments, the mixing temperature of the titanium source and the raw material ZSM-5 molecular sieve can be 4-150°C, and the mixing time can be 10min-2h. The mixing temperature of the first calcined product and the phosphorus source can be 4-150°C, and the mixing time can be 10min-2h.
[0035] In the above preparation method, the temperature of the first calcination can be 450-650°C, and the time of the first calcination can be 1h-4h. Specifically, the temperature of the first calcination can be 450°C, 500°C, 550°C, 600°C, 650°C, and other specific values, and any two of the above specific values are in the range of endpoints. The time of the first calcination is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, and other specific values, and any two of the above specific values are in the range of endpoints.
[0036] In the above preparation method, the temperature of the second calcination can be 450-650°C, and the time of the second calcination can be 1h-4h. Specifically, the temperature of the second calcination can be 450°C, 500°C, 550°C, 600°C, 650°C, and other specific values, and any two of the above specific values are in the range of endpoints. The time of the second calcination is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, and other specific values, and any two of the above specific values are in the range of endpoints.
[0037] The present invention also provides a modified ZSM-5 molecular sieve, which is obtained by the above preparation method.
[0038] In the above modified ZSM-5 molecular sieve, the modified ZSM-5 molecular sieve may include 0.2%-25% titanium and 0.2%-6% phosphorus, based on the weight of the modified ZSM-5 molecular sieve as 100%, wherein the weight of the titanium and phosphorus is calculated as oxides (titanium dioxide, phosphorus pentoxide). Further, the modified ZSM-5 molecular sieve may also include 0-5% of a modified metal element, wherein the weight of the modified metal element is calculated as oxide.
[0039] In the modified ZSM-5 molecular sieve, the weight content of titanium in the modified ZSM-5 molecular sieve is 0.2%-25%, for example, 0.5%-15%, calculated as titanium oxide. Specifically, the weight content of titanium in the modified ZSM-5 molecular sieve can be 0.2%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, and other specific values, as well as a range with any two of the above specific values as endpoints, calculated as titanium oxide.
[0040] In the modified ZSM-5 molecular sieve, the weight content of phosphorus in the modified ZSM-5 molecular sieve is 0.2%-6%, for example, 0.5%-6%, calculated as phosphorus oxide. Specifically, the weight content of phosphorus in the modified ZSM-5 molecular sieve can be 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, etc., and a range with any two of the above specific values as endpoints, calculated as phosphorus oxide.
[0041] In the modified ZSM-5 molecular sieve, the weight content of the modified metal element in the modified ZSM-5 molecular sieve is 0-5%, and can further be 0.5%-5%, calculated as the oxide of the modified metal element. Specifically, the weight content of the modified metal element in the modified ZSM-5 molecular sieve is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, and other specific values, as well as a range with any two of the above specific values as endpoints.
[0042] The present invention also provides an application of a modified ZSM-5 molecular sieve in a catalytic cracking process and / or a catalytic cracking process. The modified ZSM-5 molecular sieve has a high specific surface area retention rate after aging treatment and has high hydrothermal stability. When applied to a catalytic cracking process and a catalytic cracking process, it can promote heavy oil conversion, reduce coke formation, and has high catalytic selectivity.
[0043] The beneficial effects of the present invention are:
[0044] The modified ZSM-5 provided by the present invention has a high specific surface area retention rate after aging, and its hydrothermal stability and catalytic selectivity are significantly improved, thereby solving the adverse effects of poor stability, high coke generation and low conversion rate when the ZSM-5 molecular sieve is used. The modified ZSM-5 molecular sieve is applied in catalytic cracking process and catalytic cracking process to promote heavy oil conversion, reduce coke generation, increase total liquid recovery, and show high catalytic selectivity. DETAILED DESCRIPTION
[0045] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0046] In the present invention, the dry basis refers to the state of the material after being calcined at 800° C. for 1 hour.
[0047] The origin and specifications of the raw materials used in the embodiments and test examples of the present invention are as follows:
[0048] Waste liquid containing titanium tetrachloride: It is a waste liquid containing titanium tetrachloride produced in the preparation process of titanium-based polypropylene catalyst, provided by Lanzhou Chemical Research Center of PetroChina Petrochemical Research Institute. The waste liquid contains 90% titanium (in terms of TiCl4), 2-5% alkoxy titanium complex, and the rest is hydrocarbons in liquid state at room temperature; the main hydrocarbon is n-hexane, and the rest is esters.
[0049] Ordinary ZSM-5 molecular sieve: silicon-aluminum ratio 31, mesopore volume 0.04mL / g, industrial product, collected from Lanzhou Petrochemical Company Catalyst Plant. The appearance color of the molecule is white, and there is no template in the molecular sieve.
[0050] Micro-mesoporous ZSM-5 molecular sieve: silicon-aluminum ratio 30, mesopore volume 0.29 mL / g, commercially available, produced in Dalian. The molecular sieve has a white appearance and retains the template agent.
[0051] Titanium tetrachloride, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ferric nitrate (Fe(NO3)·3.9H2O), zirconium sulfate, polyethylene glycol, carboxymethyl cellulose: all are chemical reagents. n-Hexane: analytical grade reagent.
[0052] Ammonia water: weight concentration 18%, chemical reagent.
[0053] Kaolin (loss on ignition 18.6%), aluminum sol (containing 21.2 wt% alumina): both are industrial products, collected from the catalyst plant of Lanzhou Petrochemical Company.
[0054] In the following examples and comparative examples, the content of elements such as titanium, phosphorus, and modified metal in the samples was determined by X-ray fluorescence analysis. The crystallinity of ZSM-5 is relative crystallinity, which is measured by XRD method. The specific surface area retention rate is the ratio of the specific surface area of the modified molecular sieve before aging to the specific surface area after aging multiplied by 100%. The pore volume of the molecular sieve is measured by Micromeritics ASAP3000 automatic physical adsorption instrument, N2 isothermal adsorption-desorption.
[0055] Example 1
[0056] This embodiment provides a modified ZSM-5 molecular sieve, and the preparation method thereof is as follows:
[0057] (1) 1.402 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) was added to 4 L of deionized water, stirred evenly, and then 139 g of waste liquid containing titanium tetrachloride was added, stirred for 0.5 h to form a slurry containing the molecular sieve (as a mixed liquid), dried at 120° C., and calcined at 500° C. for 1 h; wherein the pH value of the slurry containing the molecular sieve was 1.01;
[0058] (2) The calcined product of step (1) was mixed with 4 L of deionized water, 73 g of phosphoric acid was added, stirred evenly, dried at 120 °C, and calcined at 500 °C for 1 h to obtain a titanium-phosphorus-modified micro-mesoporous ZSM-5 molecular sieve, denoted as Z-1.
[0059] Calculated based on the amount of raw materials added, the composition of the titanium-phosphorus modified micro-mesoporous ZSM-5 molecular sieve obtained in this example is: 3.5% titanium (in terms of oxide), 3.0% phosphorus (in terms of oxide), and the remainder ZSM-5 molecular sieve.
[0060] Example 2
[0061] This embodiment provides a modified ZSM-5 molecular sieve, and the preparation method thereof is as follows:
[0062] (1) 1.388 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) and 15 g of polyethylene glycol were added to 3.5 L of deionized water and stirred evenly, and then 20 g of waste liquid containing titanium tetrachloride and 103 g of zirconium sulfate were added and stirred for 1.5 h to form a slurry containing the molecular sieve, which was dried at 100 ° C. and calcined at 550 ° C. for 1.5 h; wherein the pH value of the slurry containing the molecular sieve was 1.52;
[0063] (2) The calcined product of step (1) was mixed with 15 g of polyethylene glycol and 3.5 L of deionized water, and then 97 g of phosphoric acid was added, stirred evenly, dried at 100 °C, and calcined at 550 °C for 1.5 h to obtain a titanium-zirconium-phosphorus modified micro-mesoporous ZSM-5 molecular sieve, denoted as Z-2.
[0064] Calculated based on the amount of raw materials added, the composition of the titanium-zirconium-phosphorus modified micro-mesoporous ZSM-5 molecular sieve obtained in this embodiment is: 0.5% titanium (as oxide), 4.0% phosphorus (as oxide), 3.0% zirconium (as oxide), and the remainder is ZSM-5 molecular sieve.
[0065] Example 3
[0066] This embodiment provides a modified ZSM-5 molecular sieve, and the preparation method thereof is as follows:
[0067] (1) Under stirring, 792 g of waste liquid containing titanium tetrachloride, 113.6 g of ferric nitrate, and 110 g of carboxymethyl cellulose were added to 3.6 L of deionized water, stirred for 10 min, and the pH value was adjusted to 6.51 with aqueous ammonia, and then 1.102 kg of ordinary ZSM-5 molecular sieve (dry basis) was added, stirred for 1 h to form a slurry containing molecular sieve, dried at 100 ° C, and calcined at 520 ° C for 1 h; wherein the pH value of the slurry containing molecular sieve was 5.66;
[0068] (2) The calcined product of step (1), 110 g of carboxymethyl cellulose and 3.6 L of deionized water were mixed, and 139 g of diammonium hydrogen phosphate was added. The mixture was stirred evenly, dried at 100° C., and calcined at 520° C. for 1 h to obtain a titanium iron phosphorus modified ZSM-5 molecular sieve, which was recorded as Z-3.
[0069] Calculated based on the amount of raw materials added, the composition of the titanium-iron-phosphorus modified ZSM-5 molecular sieve obtained in this embodiment is: titanium (as oxide) 20.0%, phosphorus (as oxide) 5.0%, iron (as oxide) 1.5%, and the remainder is ZSM-5 molecular sieve.
[0070] Example 4
[0071] This embodiment provides a modified ZSM-5 molecular sieve, and the preparation method thereof is as follows:
[0072] (1) Weighing 170.6 g of Fe(NO3)·3.9H2O and 107 g of waste liquid containing titanium tetrachloride and dissolving them in distilled water to prepare a mixed ferric nitrate / titanium tetrachloride impregnation solution, wherein the pH value of the mixed ferric nitrate / titanium tetrachloride impregnation solution is 0.56; slowly pouring the mixed impregnation solution into 1.381 kg of ordinary ZSM-5 molecular sieve (dry basis), stirring continuously to achieve equal volume impregnation; standing for 12 hours, drying in a 120° C. oven for 6 hours; calcining in a 540° C. muffle furnace for 4 hours to obtain a modified Fe-Ti / ZSM-5 molecular sieve;
[0073] (2) The Fe-Ti / ZSM-5 molecular sieve modified in step (1) was mixed with 3.6 L of deionized water, 73 g of diammonium phosphate was added, stirred evenly, dried at 120° C., and calcined at 520° C. for 1 h to obtain a titanium iron phosphorus modified ZSM-5 molecular sieve, denoted as Z-4.
[0074] Calculated based on the amount of raw materials added, the composition of the titanium-iron-phosphorus modified ZSM-5 molecular sieve obtained in this embodiment is: titanium (as oxide) 2.7%, phosphorus (as oxide) 3.0%, iron (as oxide) 2.25%, and the remainder is ZSM-5 molecular sieve.
[0075] Example 5
[0076] This embodiment provides a modified ZSM-5 molecular sieve, and the preparation method thereof is as follows:
[0077] (1) 1.402 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) was added to 4 L of deionized water, and stirred evenly. Then 125 g of titanium tetrachloride was added, and stirred for 0.5 h to form a slurry containing the molecular sieve (as a mixed liquid), which was dried at 120° C. and calcined at 500° C. for 1 h. The pH value of the slurry containing the molecular sieve was 1.03.
[0078] (2) The calcined product of step (1) was mixed with 4 L of deionized water, 73 g of phosphoric acid was added, stirred evenly, dried at 120 °C, and calcined at 500 °C for 1 h to obtain a titanium-phosphorus-modified micro-mesoporous ZSM-5 molecular sieve, denoted as Z-5.
[0079] Calculated based on the amount of raw materials added, the composition of the titanium-phosphorus modified micro-mesoporous ZSM-5 molecular sieve obtained in this example is: 3.5% titanium (in terms of oxide), 3.0% phosphorus (in terms of oxide), and the remainder ZSM-5 molecular sieve.
[0080] Example 6
[0081] This embodiment provides a modified ZSM-5 molecular sieve, and the preparation method thereof is as follows:
[0082] (1) Under stirring, 712 g of titanium tetrachloride, 113.6 g of ferric nitrate, 21 g of n-hexane, and 110 g of carboxymethyl cellulose were added to 3.6 L of deionized water, stirred for 10 min, the pH value was adjusted to 6.51 with aqueous ammonia, and then 1.102 kg of ordinary ZSM-5 molecular sieve (dry basis) was added, stirred for 1 h to form a slurry containing molecular sieve, dried at 100 ° C, and calcined at 520 ° C for 1 h; wherein the pH value of the slurry containing molecular sieve is 5.70;
[0083] (2) The calcined product of step (1), 110 g of carboxymethyl cellulose and 3.6 L of deionized water were mixed, and 139 g of diammonium hydrogen phosphate was added. The mixture was stirred evenly, dried at 100° C., and calcined at 520° C. for 1 h to obtain a titanium iron phosphorus modified ZSM-5 molecular sieve, which was recorded as Z-6.
[0084] Calculated based on the amount of raw materials added, the composition of the titanium-iron-phosphorus modified ZSM-5 molecular sieve obtained in this embodiment is: titanium (as oxide) 20.0%, phosphorus (as oxide) 5.0%, iron (as oxide) 1.5%, and the remainder is ZSM-5 molecular sieve.
[0085] Comparative Example 1
[0086] This comparative example provides a modified ZSM-5 molecular sieve, and its preparation method is as follows:
[0087] (1) 1.455 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) was added to 4 L of deionized water, stirred for 0.5 h to form a slurry containing the molecular sieve, dried at 120° C., and calcined at 500° C. for 1 h; wherein the pH value of the slurry containing the molecular sieve was 2.51;
[0088] (2) The calcined product of step (1) was mixed with 4 L of deionized water, 73 g of phosphoric acid was added, stirred evenly, dried at 120 °C, and calcined at 500 °C for 1 h to obtain a phosphorus-modified micro-mesoporous ZSM-5 molecular sieve, denoted as DZ-1.
[0089] Calculated based on the amount of raw materials added, the composition of the phosphorus-modified micro-mesoporous ZSM-5 molecular sieve obtained in this comparative example is: 3.0% phosphorus (in terms of oxide) and the remainder ZSM-5 molecular sieve.
[0090] Comparative Example 2
[0091] This comparative example provides a modified ZSM-5 molecular sieve, and its preparation method is as follows:
[0092] (1) 1.455 kg of ordinary ZSM-5 molecular sieve (dry basis) was added to 4 L of deionized water, stirred for 0.5 h to form a molecular sieve slurry, dried at 120 ° C, and calcined at 500 ° C for 1 h; wherein the pH value of the slurry containing the molecular sieve was 2.53;
[0093] (2) The calcined product of step (1) was mixed with 4 L of deionized water, 73 g of phosphoric acid was added, stirred evenly, dried at 120° C., and calcined at 500° C. for 1 h to obtain a phosphorus-modified ZSM-5 molecular sieve, which was recorded as DZ-2.
[0094] Calculated based on the amount of raw materials added, the composition of the phosphorus-modified ZSM-5 molecular sieve obtained in this comparative example is: phosphorus (in terms of oxide) 3.0%, and the balance is ZSM-5 molecular sieve.
[0095] Comparative Example 3
[0096] This comparative example provides a modified ZSM-5 molecular sieve, and its specific preparation method is as follows:
[0097] 170.6 g of Fe(NO3)·3.9H2O and 96 g of titanium tetrachloride were dissolved in an appropriate volume of distilled water to prepare a ferric nitrate / titanium tetrachloride mixed impregnation solution, and the mixed impregnation solution was slowly poured into 1.426 kg of ordinary ZSM-5 molecular sieve (dry basis) with continuous stirring to achieve equal volume impregnation; after standing for 12 hours, it was placed in a 120°C oven and dried for 6 hours; and calcined in a 540°C muffle furnace for 4 hours to obtain a titanium-iron modified ZSM-5 molecular sieve, recorded as DZ-3.
[0098] Calculated based on the amount of raw materials added, the composition of the titanium-modified ZSM-5 molecular sieve obtained in this comparative example is: 2.7% titanium (in terms of oxide), 2.25% iron (in terms of oxide), and the remainder ZSM-5 molecular sieve.
[0099] Comparative Example 4
[0100] This comparative example provides a modified ZSM-5 molecular sieve, and its preparation method is as follows:
[0101] (1) 1.402 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) was added to 4 L of deionized water, stirred evenly, and then 73 g of phosphoric acid was added, stirred evenly, dried at 120 ° C, and calcined at 500 ° C for 1 h;
[0102] (2) The calcined product of step (1) was mixed with 4 L of deionized water, 139 g of waste liquid containing titanium tetrachloride was added, and the mixture was stirred for 0.5 h to form a slurry containing molecular sieves. The mixture was stirred evenly, dried at 120 ° C, and calcined at 500 ° C for 1 h to obtain a phosphorus-titanium modified micro-mesoporous ZSM-5 molecular sieve, which was recorded as DZ-4.
[0103] Calculated based on the amount of raw materials added, the composition of the phosphorus-titanium modified micro-mesoporous ZSM-5 molecular sieve obtained in this comparative example is: 3.5% titanium (in terms of oxide), 3.0% phosphorus (in terms of oxide), and the remainder ZSM-5 molecular sieve.
[0104] Test Example 1
[0105] This test example is used to provide the test results of the hydrothermal stability of the modified ZSM-5 molecular sieves prepared in the above examples and comparative examples.
[0106] The modified ZSM-5 molecular sieves Z-1, Z-2, Z-3, and Z-4 prepared in Examples 1 to 4 and the modified ZSM-5 molecular sieves DZ-1, DZ-2, and DZ-3 prepared in Comparative Examples 1 to 3 were respectively used as samples to be tested, and the specific surface areas of the samples to be tested were measured; then, each sample to be tested was aged for 17 hours at 800° C. and 100% water vapor, and the specific surface areas of the samples to be tested after aging were measured, and the specific surface area retention rate was calculated. The results are listed in Table 1.
[0107] Table 1 Specific surface area retention test results of ZSM-5 molecular sieves of Examples 1-6 and Comparative Examples 1-4
[0108]
[0109] The results in Table 1 show that after aging at 800° C. and 100% steam for 17 hours, the specific surface area retention rate of the ZSM-5 molecular sieve prepared by the preparation method of the present invention is higher than that of the comparative ZSM-5 molecular sieve prepared in the comparative example.
[0110] The difference between Example 1 and Comparative Example 1 is only whether a titanium source is added. The specific surface area retention rate of the titanium-phosphorus modified ZSM-5 molecular sieve of Example 1 is 11.7% higher than that of the phosphorus-modified ZSM-5 molecular sieve of Comparative Example 1.
[0111] The modifying elements used in Example 4 and Comparative Example 3 are different, and phosphorus is not used to modify the molecular sieve in Comparative Example 3. By comparison, it can be seen that the specific surface area retention rate of the titanium iron phosphorus modified ZSM-5 molecular sieve in Example 4 is 10.4% higher than the specific surface area retention rate of the titanium iron modified ZSM-5 molecular sieve in Comparative Example 3.
[0112] The difference between Comparative Example 4 and each embodiment (especially Example 5) is that the modification order of the phosphorus source and the titanium source is different. As can be seen from Table 1, compared with first modifying the ZSM-5 molecular sieve with phosphorus and then modifying the ZSM-5 molecular sieve with titanium, the reaction order of first modifying the ZSM-5 molecular sieve with titanium and then modifying the ZSM-5 molecular sieve with phosphorus adopted in the present invention can significantly improve the specific surface area retention rate of the molecular sieve, and the increase can reach more than 8 percentage points. The above results show that the present invention can effectively improve the hydrothermal stability of the ZSM-5 molecular sieve by controlling the reaction order.
[0113] The types of titanium sources used in Example 1 and Example 5 are different. It can be seen from Table 1 that pure titanium tetrachloride (Example 5) and waste liquid containing titanium tetrachloride (Example 1) as titanium sources for modifying molecular sieves can improve the specific surface area retention rate of molecular sieves to a certain extent; among them, compared with pure titanium tetrachloride, waste liquid containing titanium tetrachloride as a titanium source has a more obvious effect of improving hydrothermal stability.
[0114] The above results indicate that the preparation method of the present invention can significantly improve the hydrothermal stability of the titanium-phosphorus-modified ZSM-5 molecular sieve obtained by combining titanium and phosphorus as modifying elements and controlling the reaction order; on this basis, the performance of the ZSM-5 molecular sieve can be further improved by using iron, zirconium, zinc, magnesium, calcium, zirconium, lanthanum, cerium, and yttrium as the second metal for modification.
[0115] Test Example 2
[0116] This test example provides the analysis results of the elemental composition of the modified ZSM-5 molecular sieves of the above embodiments and comparative examples. The content of each element in the samples of the above embodiments and comparative examples was tested by X-ray fluorescence analysis, the weight content of titanium, phosphorus, iron, and zirconium elements was calculated as oxide, and the weight content of chlorine element was calculated as Cl element, and the test results are summarized in Table 2.
[0117] Table 2 Analysis results of element contents of modified ZSM-5 molecular sieves of Examples 1-6 and Comparative Examples 1-4
[0118]
[0119]
[0120] The main difference between Comparative Example 4 and each embodiment (especially Example 1) is that in Comparative Example 4, the ZSM-5 molecular sieve is first modified with phosphorus and then with titanium, while in the embodiment, the ZSM-5 molecular sieve is first modified with titanium and then with phosphorus. The results show that the Cl content in the modified ZSM-5 molecular sieves of each embodiment is close to 0, while the Cl content in the modified ZSM-5 molecular sieve of Comparative Example 4 is more than 7%, indicating that the modified ZSM-5 molecular sieve prepared by the embodiment of the present invention contains fewer impurities, and further indicating that the reaction sequence of the present invention can effectively reduce the impurity content in the modified ZSM-5 molecular sieve and improve the quality of the molecular sieve. In the catalytic cracking reaction process, if the chlorine content on the molecular sieve and the catalyst is too high, it is easy to cause corrosion and salt formation of the catalytic cracking unit, which is not conducive to the long-term stable operation of the device.
[0121] The appearance color of the modified ZSM-5 molecular sieve (first titanium modification, then phosphorus modification) of each embodiment is white, while the appearance color of the modified ZSM-5 molecular sieve (first phosphorus modification, then titanium modification) of comparative example 4 is gray. This result shows that the template agent in the modified ZSM-5 molecular sieve of comparative example 4 is not easy to remove, and the template agent will block the molecular sieve pores, which has an adverse effect on the catalytic process; and the template agent in the modified ZSM-5 molecular sieve prepared by the present invention is easily removed by the roasting process, so as to avoid the situation that the template agent blocks the molecular sieve pores, which is conducive to improving the catalytic reaction selectivity of the molecular sieve. The measurement result of pore volume also shows that the pore volume of the modified ZSM-5 molecular sieve prepared in comparative example 4 is 0.25mL / g, and the pore volume of the modified ZSM-5 molecular sieve prepared in Example 1 is 0.31mL / g, indicating that the modified ZSM-5 molecular sieve prepared by the present invention has a relatively smooth pore structure.
[0122] The crystallinity of the ZSM-5 molecular sieves of the modified ZSM-5 molecular sieves of Example 1, Example 2, Example 5, Comparative Example 1 and Comparative Example 4 was analyzed and tested, and the crystallinity results of each molecular sieve are as follows: the crystallinity of the molecular sieve of Example 1 is 65%, the crystallinity of the molecular sieve of Example 2 is 66%, the crystallinity of the molecular sieve of Example 5 is 65%, the crystallinity of the molecular sieve of Comparative Example 1 is 60%, and the crystallinity of the molecular sieve of Comparative Example 4 is 63%. The main difference between Comparative Example 1 and Example 1 and Example 2 is that Comparative Example 1 only uses phosphorus-modified ZSM-5 molecular sieves and does not use titanium modification. The molecular sieve is subjected to high-temperature calcination during the modification process, which will cause the dealumination and structural destruction of the molecular sieve, so that the crystallinity of the molecular sieve measured by XRD is reduced, so the level of the crystallinity of the molecular sieve in the modified product can reflect the stability of the molecular sieve. Compared with the modified ZSM-5 molecular sieve prepared in Comparative Example 1, the crystallinity of the ZSM-5 molecular sieve in the modified ZSM-5 molecular sieves of Example 1, Example 2, and Example 5 is increased by more than 5 percentage points, indicating that the synergistic modification of titanium and phosphorus makes the modified ZSM-5 molecular sieve prepared by the present invention better than the modified ZSM-5 molecular sieve of Comparative Example 1. The crystallinity of the ZSM-5 molecular sieve in the modified ZSM-5 molecular sieve of Example 1 is increased by 2 percentage points, while the crystallinity of the ZSM-5 molecular sieve in the modified ZSM-5 molecular sieve of Comparative Example 4 is relatively low, at 63%. This result also shows that the modified ZSM-5 molecular sieve prepared by the present invention is better than the modified ZSM-5 molecular sieve of Comparative Example 4. The above results show that the stability of the ZSM-5 molecular sieve can be effectively improved by synergistically modifying the ZSM-5 molecular sieve with titanium and phosphorus (further modification of modified metals such as zirconium can also be performed) and controlling the modification order.
[0123] Test Example 3
[0124] This test example provides a catalytic performance test of the modified ZSM-5 molecular sieves of the above embodiments and comparative examples.
[0125] First, the modified ZSM-5 molecular sieve of the above-mentioned embodiment and comparative example was used as the active component to prepare a catalytic cracking aid containing the modified ZSM-5 molecular sieve. The preparation method of the catalytic cracking aid is as follows:
[0126] 132g of kaolin (on a dry basis), 54g of aluminum sol (on alumina basis) and 345mL of deionized water were added to a slurrying tank for slurrying, stirred for 0.5h, and then 114g of modified ZSM-5 molecular sieve (on a dry basis) was added, mixed and slurried for 0.5h, and the obtained slurry was sand milled, spray dried, and calcined at 550°C for 2h to obtain a catalytic cracking aid. The particle size of the catalytic cracking aid is 65μm-78μm.
[0127] The composition of the catalytic cracking aid is: 38 wt% (on a dry basis) of modified ZSM-5 molecular sieve, 44 wt% (on a dry basis) of kaolin, and 18 wt% of alumina from aluminum sol.
[0128] Industrial catalyst with industrial grade LDC-200QH was uniformly mixed with catalytic cracking aid in a weight ratio of 9:1 to obtain 10 groups of catalyst mixtures. After aging treatment at 800°C and 100% water vapor for 17 hours, the catalytic cracking reaction performance of the 10 groups of catalyst mixtures was evaluated on a heavy oil micro-reactor evaluation device (ACE).
[0129] The results of the catalytic cracking reaction selectivity evaluation of the catalytic cracking aids containing the modified ZSM-5 molecular sieves of the above examples and comparative examples are summarized in Table 3. In Table 3, total liquid yield = liquefied gas yield + gasoline yield + diesel yield; coke factor = (100-conversion rate) × coke yield / conversion rate.
[0130] Table 3 Reaction performance test of modified ZSM-5 molecular sieves of Examples 1-6 and Comparative Examples 1-4
[0131]
[0132] From the results in Table 3, it can be seen that the modified ZSM-5 molecular sieve auxiliary provided by the present invention has a high conversion rate, which can reach more than 84.92%; low heavy oil, which can be controlled below 5.03%; less coke, which can be controlled below 8.6%; high total liquid recovery, which can reach more than 83%; low coke factor, which can be controlled below 1.50. The above test results show that the modified ZSM-5 molecular sieve provided by the present invention has good reaction selectivity and good catalytic effect.
[0133] Furthermore, the modified ZSM-5 molecular sieves prepared in Examples 1 to 6 all have high catalytic selectivity, among which the selectivity of the modified ZSM-5 molecular sieves prepared in Examples 1 and 3 is higher than the catalytic selectivity of the molecular sieves prepared in Examples 5 and 6, respectively. This result indicates that, relative to analytically pure titanium tetrachloride and a combination of analytically pure titanium tetrachloride and n-hexane, waste liquid containing titanium tetrachloride as a titanium source can further enhance the modification effect.
[0134] The above test results show that compared with the existing ZSM-5 molecular sieve, the modified ZSM-5 molecular sieve prepared by the above method of the present invention has good hydrothermal stability and good catalytic reaction selectivity, is suitable for use in catalytic cracking and catalytic cracking catalysts under high-temperature hydrothermal reaction environments, and has high practical value.
Claims
1. A method for preparing a modified ZSM-5 molecular sieve, the method comprising: The titanium source and the raw material ZSM-5 molecular sieve are mixed to form a mixed solution, and a first calcination is performed; Alternatively, the raw material ZSM-5 molecular sieve is fully impregnated with an impregnation solution containing a titanium source, dried, and subjected to a first calcination; The product of the first calcination is mixed with a phosphorus source and subjected to a second calcination to obtain the modified ZSM-5 molecular sieve.
2. The preparation method according to claim 1, wherein The titanium source includes titanium tetrachloride.
3. The preparation method according to claim 1, wherein The titanium source comprises titanium tetrachloride and hexane in a weight ratio of (4-34):1; Preferably, the titanium source comprises a waste liquid containing titanium tetrachloride; Preferably, the waste liquid containing titanium tetrachloride is the waste liquid containing titanium tetrachloride obtained in the production process of titanium-based polyolefin catalyst.
4. The preparation method according to claim 1, wherein The phosphorus source includes one or a combination of two or more of phosphoric acid, phosphate, phosphorous acid, phosphite, pyrophosphoric acid, pyrophosphate, polyphosphoric acid, polyphosphate, metaphosphoric acid, and metaphosphate; Preferably, the phosphorus source includes one or a combination of two or more of phosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen phosphate, magnesium phosphate, aluminum phosphate, phosphorous acid, ammonium phosphite, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.
5. The preparation method according to claim 1, wherein Taking the weight of the modified ZSM-5 molecular sieve as 100%, the modified ZSM-5 molecular sieve comprises 0.2%-25% of titanium and 0.2%-6% of phosphorus, wherein the weights of the titanium and phosphorus are calculated as oxides.
6. The preparation method according to claim 5, wherein: The modified ZSM-5 molecular sieve also includes a modified metal element; the modified metal element includes one or a combination of two or more of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium.
7. The preparation method according to claim 6, wherein: Calculated as oxide of the modified metal element, the weight content of the modified metal element in the modified ZSM-5 molecular sieve is 0-5%.
8. The preparation method according to claim 1, wherein The pH value of the mixed solution and / or the impregnation solution is 0.5-8; Preferably, the pH value of the mixed solution and / or the impregnating solution is 0.5-3.
9. The preparation method according to claim 1 or 8, wherein: The mixed solution and / or the impregnating solution also includes a dispersant; the weight of the dispersant is 0-20% of the weight of the raw molecular sieve.
10. The preparation method according to claim 1, wherein: The temperature of the first calcination is 450-650° C., and the time of the first calcination is 1 h-4 h; The temperature of the second calcination is 450-650° C., and the time of the second calcination is 1 h-4 h.
11. A modified ZSM-5 molecular sieve, wherein the modified ZSM-5 molecular sieve is obtained by the preparation method according to any one of claims 1 to 10.
12. Use of the modified ZSM-5 molecular sieve according to claim 11 in a catalytic cracking process and / or a catalytic cracking process.
Citation Information
Patent Citations
Method for improving B acid content of ZSM-5 molecular sieve and realizing yield increase of light olefin
CN102114429A
Propylene polymerization catalyst
CN102336851A
Polypropylene catalyst component, preparation method and catalyst
CN107434832A
Olefinic polymeric carrier catalyst system and preparation method thereof
CN1110281A
Production of olefins
US5171921A